Quantum bouncer with dissipation - G. González (Revista Mexicana de Física, 2006)
Effects on the spectra of the quantum bouncer due to dissipation are given when a linear o quadratic dissipation in the velocity of the particle is taken into account. Classical constants of motion and Hamiltonians are deduced for these systems and their quantized eigenvalues are estimated through perturbation theory. Differences were found comparing the eigenvalues of the constants of motion and the eigenvalues of the Hamiltonians. The cases when the dissipation parameters go to zero are compared with the nondissipative cases.